2022
DOI: 10.1371/journal.pgph.0000112
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing public health? Factors affecting the issuance of stay-at-home orders in response to COVID-19 in Africa

Abstract: COVID-19 has sickened and killed millions of people globally. Conventional non-pharmaceutical interventions, particularly stay-at-home orders (SAHOs), though effective for limiting the spread of disease have significantly disrupted social and economic systems. The effects also have been dramatic in Africa, where many states are already vulnerable due to their developmental status. This study is designed to test hypotheses derived from the public health policymaking literature regarding the roles played by medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…By April 30, 2020, the U.S. Center for Disease Control and Prevention (CDC, 2021) reported more than 60,000 cumulative deaths in the U.S. from COVID-19 with about 30,000 new cases per day. Globally, governments often took dramatic steps in response to the disease (e.g., Carr et al, 2022; Murray & Rutland, 2022). Impacts from the pandemic and related government responses were widely felt with as much as a third of the world’s population under some type of lockdown or quarantine by April of 2020 (Kaplan et al, 2020; Walters, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…By April 30, 2020, the U.S. Center for Disease Control and Prevention (CDC, 2021) reported more than 60,000 cumulative deaths in the U.S. from COVID-19 with about 30,000 new cases per day. Globally, governments often took dramatic steps in response to the disease (e.g., Carr et al, 2022; Murray & Rutland, 2022). Impacts from the pandemic and related government responses were widely felt with as much as a third of the world’s population under some type of lockdown or quarantine by April of 2020 (Kaplan et al, 2020; Walters, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…That is, the four most important variables identified by the machine learning classifier were originally identified in theory-based research (e.g., Ref. [ 29 ]. More broadly, we found that external forces, particularly temporal diffusion, made the strongest contribution to the prediction of SAHOs.…”
Section: Discussionmentioning
confidence: 99%
“…The dependent/outcome variable is sahoStatus , which is coded 1 when a country had issued a SAHO and 0 when it had not. Overall, 41 countries issued a SAHO, and 13 did not between January 31 and June 15, 2020 [ 29 ]. January 31 is the day after the WHO declared a public health emergency related to COVID-19, and June 15 is approximately 30 days after the last African country issued a SAHO during the first wave of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…What is interesting is that current understandings of governments’ policies regarding movement during the COVID-19 pandemic have largely assumed that higher levels of movement result from weaker governing capacity (e.g., Murray & Joshua, 2022 ). While districts with Hezbollah private governance observed lower reductions in movement compared to districts without Hezbollah private governance, this does not necessarily mean that governance was lacking.…”
Section: Discussionmentioning
confidence: 99%